2019
DOI: 10.1136/bjsports-2019-100710
|View full text |Cite
|
Sign up to set email alerts
|

Mental health symptoms and disorders in elite athletes: a systematic review on cultural influencers and barriers to athletes seeking treatment

Abstract: ObjectiveTo summarise the literature on the barriers to athletes seeking mental health treatment and cultural influencers of mental health in elite athletes.DesignSystematic reviewData sourcesPubMed, Cochrane, Scopus, SportDiscus (Ebsco), and PsycINFO (ProQuest) up to November 2018.Eligibility criteria for selecting studiesQualitative and quantitative original studies of elite athletes (those who competed at the professional, Olympic, or collegiate/university levels), published in any language.ResultsStigma, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
134
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(140 citation statements)
references
References 82 publications
(122 reference statements)
3
134
0
3
Order By: Relevance
“…This is in line with previous research which found that lack of time was a chief barrier to help-seeking in college athletes (López and Levy, 2013). Together this highlights the importance of making appropriate services and sources of help available and accessible to athletes taking into account their demanding schedules, time constraints and needs (López and Levy, 2013;Castaldelli-Maia et al, 2019).…”
Section: Personal Characteristics and Attitudessupporting
confidence: 89%
See 3 more Smart Citations
“…This is in line with previous research which found that lack of time was a chief barrier to help-seeking in college athletes (López and Levy, 2013). Together this highlights the importance of making appropriate services and sources of help available and accessible to athletes taking into account their demanding schedules, time constraints and needs (López and Levy, 2013;Castaldelli-Maia et al, 2019).…”
Section: Personal Characteristics and Attitudessupporting
confidence: 89%
“…This suggests that changing the culture to allow elite athletes to be more open may facilitate help-seeking. Coaching staff have an important role to play in ensuring a supportive culture in which help-seeking is encouraged (Castaldelli-Maia et al, 2019).…”
Section: Personal Characteristics and Attitudesmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite efforts to bring awareness to the issue of mental health, normative and socially reinforced reluctance to seek help has persisted 34. Coaches have the potential to help shape team cultures that normalise, destigmatise and are supportive of mental health help-seeking,6 35 which may function as a form of primary prevention by shifting the willingness of team members to seek care should their own mental health challenges arise.…”
Section: Resultsmentioning
confidence: 99%